2012
DOI: 10.1002/lapl.201110125
|View full text |Cite
|
Sign up to set email alerts
|

Electrical pulse - mediated enhanced delivery of silver nanoparticles into living suspension cells for surface enhanced Raman spectroscopy

Abstract: Electrical pulse‐mediated enhanced silver nanoparticles delivery is a much better method for intracellular surfaceenhanced Raman spectroscopy (SERS) measurements of suspension cells. Robust and high‐quality SERS spectra of living suspension cells were obtained based on an electroporationSERS method, which can overcomes the shortcoming of nonuniform distribution of silver nanoparticles localized in the cell cytoplasm after electroporation and reduces the amount variance of silver nanoparticles delivered into di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…517 Exogenous SERS substrates can be incorporated into the cell using cellular uptake, electroporation, nanoinjection and similar mechanisms. 518-521 …”
Section: Raman Imagingmentioning
confidence: 99%
“…517 Exogenous SERS substrates can be incorporated into the cell using cellular uptake, electroporation, nanoinjection and similar mechanisms. 518-521 …”
Section: Raman Imagingmentioning
confidence: 99%
“…In fact, differences in uptake are not digital (i.e., "yes" or "no"), but rather are based on different kinetics. However, non-adhesive cell lines, i.e., cell suspensions, can be different and examples in which no significant internalization of NPs happened are reported [31]. Coming back to adhesive cell-lines, the first step in NP internalization obviously is the contact of the NP with the cell plasma membrane.…”
Section: Reviewmentioning
confidence: 99%
“…The potential of Raman spectroscopy for the analysis of effects of external agents (anticancer drugs, nanoparticles and CNT) on the cell has been demonstrated [21][22][23][24][25][26]. Candeloro et al reported the cytotoxic effects of Ag and Fe 3 O 4 nanoparticles on HeLa cells using Raman spectroscopy [27].…”
Section: Introductionmentioning
confidence: 99%